Plesionika edwardsii Brandt 1851 - Cardoso, Irene (Zenodo, 2009)
Plesionika edwardsii (Brandt, 1851) (Figs. 1, 2) Pandalus narval – H. Milne Edwards, 1837: 385 (not Astacus narval Fabricius, 1787). Pandalus (Pontophilus) edwardsii Brandt, 1851: 122. Pandalus (Parapandalus) longirostris Borradaile, 1899: 413, pl.37, fig.10. Plesionika edwardsii – Holthuis, 1947: 316; Pequenat, 1970: 93; Omori, 1971: 241; Crosnier & Forest, 1973: 202, fig. 63b, 64b; Chace, 1985:62, fig. 26; Crosnier, 1986: 362; Kensley et al. , 1987: 314; Chan & Yu, 1991: 550, figs. 2, 3b; Chan & Crosnier, 1997: 193, fig. 23; Cabral et al. , 2000: 246; Cruz & Fransen, 2004: 141; Viana et al. , 2007: 36. Material examined: REVIZEE: E- 0 511, 15o42’S, 38o37’W, 251 m, 8 males (13–22 mm), 10 females (20.5–26 mm), MNRJ 14655; D-0538, 13o08’S, 38o24’W, 623 m, 1 female (15 mm), MNRJ 21425. FURG: R 0 1, st. 24, 33o27’S / 50o 15’W, 108m, 21 males (12.3–17.2mm), 18 ovigerous females (16.4–20.6mm), 0 4 females (14.2–17.2mm), FURG 3252. Description: Rostrum long, curved downwards in proximal region, and upwards beyond antennular peduncle; far overreaching scaphocerite, 1.7–2.3 (avg. 1.97, n=12) times as long as carapace; ventral margin, with 30–49 (avg. 42, n=12) teeth closely disposed, dorsal margin with 19–33 (avg. 28, n=12) teeth, the anterior larger and well spaced, posterior closely spaced; two or three post-rostral teeth, the proximal one small and variably movable; eye subspherical, pear like, with ocellus; strong antennal and pterygostomian spines present; carapace smooth, without carinae (Fig. 1 A). Stylocerite acute, outer margin slightly concave, inner margin convex, overreaching the distal margin of first antennular peduncle article (Fig. 1 B). Scaphocerite 0.7–1.0 (avg. 0.9, n=14) as long as carapace, distal tooth not overreaching blade (Fig. 1 C). Maxilliped 3 with epipod, penultimate segment 0.96–1.1 (avg. 1.0, n=14) times longer than terminal segment. Pereopods 1 and 2 without epipod, pereopods 3 and 4 with reduced epipod, pereopod 5 without epipod. Pereopod 2 chelate, equal in size (Fig. 1 ...